2019
DOI: 10.1016/s0140-6736(18)32752-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy plus cisplatin or cetuximab in low-risk human papillomavirus-positive oropharyngeal cancer (De-ESCALaTE HPV): an open-label randomised controlled phase 3 trial

Abstract: SummaryBackgroundThe incidence of human papillomavirus (HPV)-positive oropharyngeal cancer, a disease affecting younger patients, is rapidly increasing. Cetuximab, an epidermal growth factor receptor inhibitor, has been proposed for treatment de-escalation in this setting to reduce the toxicity of standard cisplatin treatment, but no randomised evidence exists for the efficacy of this strategy.MethodsWe did an open-label randomised controlled phase 3 trial at 32 head and neck treatment centres in Ireland, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
600
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 758 publications
(696 citation statements)
references
References 26 publications
28
600
1
13
Order By: Relevance
“…Although only 8% of the low‐risk group in RTOG‐0129 experienced LRF, 14% in RTOG‐0522 experienced LRF; nevertheless, the rate of distant metastases remained similar (8% vs 6%). It is possible that the addition of cetuximab, which has been established as being inferior to cisplatin in 2 randomized prospective studies, to a treatment arm in RTOG‐0522 accounted for the observed differences in LRF (see Supporting Table 3). Of the 20 patients in RTOG‐0522 with LRF, approximately 65% received cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…Although only 8% of the low‐risk group in RTOG‐0129 experienced LRF, 14% in RTOG‐0522 experienced LRF; nevertheless, the rate of distant metastases remained similar (8% vs 6%). It is possible that the addition of cetuximab, which has been established as being inferior to cisplatin in 2 randomized prospective studies, to a treatment arm in RTOG‐0522 accounted for the observed differences in LRF (see Supporting Table 3). Of the 20 patients in RTOG‐0522 with LRF, approximately 65% received cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NCDB codes for biologic agents, the specific use of cetuximab cannot be confirmed; there are few other recognized biologic options for nonmetastatic OPSCC. Nevertheless, it is now being appreciated that a replacement strategy may not be optimal based on results of the Radiation Therapy Oncology Group 1016 study as well as a published randomized trial from Europe …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is now being appreciated that a replacement strategy may not be optimal based on results of the Radiation Therapy Oncology Group 1016 study 27 as well as a published randomized trial from Europe. 28 It is noteworthy that reduced-dose RT was delivered less frequently to patients receiving systemic therapy, implying a more full-scale paradigm of de-escalated therapy (i.e., both RT and systemic therapy reduction) rather than de-escalating one modality. However, it is also possible that clinicopathologic factors were more favorable in patients receiving de-escalated therapy, which could have dampened potentially worse survival in omitting systemic therapy or full-dose RT.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a multinational, randomized trial, cetuximab‐RT showed a significant improvement in survival compared with RT alone . However, two large prospective trials in patients with HPV+ HNSCC patients have shown cetuximab‐RT to be inferior to cisplatin‐RT . Many prospective HNSCC trials have evaluated different combination strategies with RT, but no doublet‐RT regimen has demonstrated superiority over cisplatin‐RT .…”
Section: Concurrent Radiation With Anti‐pd1/pd‐l1 Therapy For Hnsccmentioning
confidence: 99%
“…65 However, two large prospective trials in patients with HPV+ HNSCC patients have shown cetuximab-RT to be inferior to cisplatin-RT. 66,67 Many prospective HNSCC trials have evaluated different combination strategies with RT, but no doublet-RT regimen has demonstrated superiority over cisplatin-RT. 68,69 It should be noted, however, that cisplatin/RT may be associated with several delayed cisplatin-related toxicities, including ototoxicity, nephrotoxicity, and neurotoxicity.…”
Section: Concurrent Radiation With Anti-pd1/pd-l1 Therapy For Hnsccmentioning
confidence: 99%